Survey of various data duplication method and security algorithm issue in cloud computing (International Journal of Advanced Research in Science, Management and Technology, 2023)
Resource sharing in a pure plug and play model that dramatically simplifies infrastructure planning is the promise of „cloud computing‟. The two key advantages of this model are ease of-use and cost-effectiveness. Though there remain questions on aspects such as security and vendor lock-in, the benefits this model offers are many. This paper explores some of the basics of cloud computing with the aim of introducing aspects such as: Realities and risks of the model Components in the model Characteristics and Usage of the model The paper aims to provide a means of understanding the model and exploring options available for complementing your technology and infrastructure needs. Internet and network application are growing very fast and use of cloud computing has increased rapidly in today’s world. cloud computing offers a new way to deliver services by rearranging resources over the Internet and providing them to users on demand. It plays an important role in supporting data storage, processing, and management in the Internet of Things (IoT). Various cloud service providers (CSPs) offer huge volumes of storage to maintain and manage IoT data, which can include videos, photos, and personal health records. Cloud computing provides many advantages such as reducing ost, n-line, on-demand services and accessibility of data. Cloud computing defined different computing idea which includes huge number of peripheral device connected with real time communication like internet in computer networking. Now days due to benefited in storage technology and networking, larger function of data is being maintained in digital form. Similar data storage in disk is responsible for unnecessary storage space of data. Data de-duplication is effective way to reduce the storage space and optimize the utilization of storage space. Duplication records appear when uniform storage technique is used in data base. Identification of duplicate data is time consuming. In this paper we concentrate about data de-duplication technique and security mechanism because Organizations are transferring important information to the Cloud that increases concern over security of data.  Cryptography is common approach to protect the sensitive information in Cloud. Encryption algorithm plays a main role in information security system. In this survey paper we examine bout various security algorithm comparison.
Keywords: loud Computing, Data De-duplication, Cloud Storage, Internet of Things (IoT), Cryptography, Data Security, Storage Optimization, Encryption Algorithms.